Effect of Formic Acid Supplementation on Some Serum Biochemical Parameters of Broiler Chickens - Al-Fadhli, Murad Kadhim Mohammed; Abbas, Noura Qusay; Jalil, Mustafa Jawad (Journal of agricultural, environmental and veterinary sciences, 2018)
The aim of this study was to evaluate the effect of adding different concentrations of the formic acid to the drinking water on some serum biochemical parameters of broiler chickens aged between 21 and 42 days. In a completely randomized design, Eighty-four, one-day-old broiler chicks were divided into 4 groups with three replicates of each group and seven birds per each replicate. The organic formic acid was added to the drinking water in the following concentration (0.1%, 0.2%, and 0.3%) represented the treatment group (T2, T3 and T4) respectively, while in the control group (T1); the drinking water was free of formic acids. Blood samples were collected at age of 21 and 42 days. At age of 21 days, data indicated that the first treatment group (T2) was showed a significant increase (P≤0.05) in serum total protein and albumin and significant decrease (P≤0.05) in each of serum cholesterol, triglycerides and serum glucose. The second treatment group (T3) was also showed a significant increase (P≤0.05) in serum total protein and albumin, in addition to serum cholesterol but it was showed a significant decrease (P≤0.05) in both of serum triglycerides and serum glucose. Whereas the third treatment group (T4) was showed a significant increase (P≤0.05) in each of serum total protein, albumin, cholesterol, and serum triglycerides, but it was showed non-significant differences (P˃0.05) in serum glucose concentration. The result of the blood samples that were collected at 42 days of age indicated a presence of a significant decrease (P≤0.05) in serum total protein level and non-significant differences (P˃0.05) in both of serum albumin and serum cholesterol level, but it was showed a significant increase (P≤0.05) in both serum triglycerides and glucose levels in the first treatment group (T2). The second treatment group (T3) showed a significant increase (P≤0.05) in each of serum total protein, triglycerides and serum cholesterol levels, but it was showed non-significant differences (P˃0.05) in serum albumin level and non-significant decrease (P˃0.05) in serum glucose levels. The result from the third treatment group (T4) indicated non-significant differences (P˃0.05) in each of serum total protein, albumin, and serum cholesterol levels, and a non-significant decrease in serum glucose levels. These results showed the importance of adding organic formic acid to the drinking water on the improvement of some serum biochemical parameters of broiler chickens.
Keywords: Formic acid; Serum biochemical parameters; Broiler chickens